2020
DOI: 10.1002/nau.24440
|View full text |Cite
|
Sign up to set email alerts
|

Brain nitric oxide induces facilitation of the micturition reflex through brain glutamatergic receptors in rats

Abstract: Aim Brain nitric oxide (NO) have been reported in regulation of the sympatho‐adrenomedullary system, which can affect voiding and storage functions. Therefore, we investigated effects of intracerebroventricularly (icv) administered 3‐(4‐morpholinyl)sydnonimine, hydrochloride (SIN‐1) (NO donor) on the micturition reflex, focusing on their dependence on the sympatho‐adrenomedullary system and on brain N‐methyl‐D‐aspartate (NMDA) and α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazole propionate (AMPA) receptors in urethane‐a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…4), which abolished the SIN-1-induced plasma adrenaline elevation in rats. 139 Since Masuda et al reported that centrally administered L-NAME (NO synthase inhibitor) inhibited micturition in anesthetized rats, 140 our data in anesthetized rats show that brain NO can induce frequent urination, independently of the sympathoadrenomedullary outflow, a representative stress response.…”
Section: Nomentioning
confidence: 66%
See 3 more Smart Citations
“…4), which abolished the SIN-1-induced plasma adrenaline elevation in rats. 139 Since Masuda et al reported that centrally administered L-NAME (NO synthase inhibitor) inhibited micturition in anesthetized rats, 140 our data in anesthetized rats show that brain NO can induce frequent urination, independently of the sympathoadrenomedullary outflow, a representative stress response.…”
Section: Nomentioning
confidence: 66%
“…4), and reduced BC and SVV without changing RV, and the SIN‐1‐induced ICI shortening was not influenced by ADX (Fig. 4), which abolished the SIN‐1‐induced plasma adrenaline elevation in rats 139 . Since Masuda et al .…”
Section: Possible Brain Molecules Related To Stress‐induced Effects On Urinary Function: Our Neuropharmacological Studiesmentioning
confidence: 81%
See 2 more Smart Citations